2001
DOI: 10.1089/104303401750195845
|View full text |Cite
|
Sign up to set email alerts
|

In VivoGene Transfer in Mouse Skeletal Muscle Mediated by Baculovirus Vectors

Abstract: Baculovirus vectors are efficient tools for gene transfer into mammalian cells in vitro. However, in vivo gene delivery by systemic administration is hindered by the vector inactivation mediated by the complement system. To characterize further the gene transfer efficacy of baculovirus we examined the vector transduction efficiency in skeletal muscle. Vectors expressing vesicular stomatitis virus glycoprotein (VSV-G) in the viral envelope were generated by inserting the VSV-G coding sequence downstream of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 37 publications
4
97
0
4
Order By: Relevance
“…Previously, it has been shown that they possess the capacity to transduce a variety of mammalian cell types including mesenchymal cells, neural glial cells and hepatocytes. [1][2][3][4][14][15][16][17] Our results show that baculoviruses are able to transduce brain cells efficiently in vivo and possess a very specific cell tropism in rat brain. The choroid plexus epithelial cells were transduced with high efficiency (Figure 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that they possess the capacity to transduce a variety of mammalian cell types including mesenchymal cells, neural glial cells and hepatocytes. [1][2][3][4][14][15][16][17] Our results show that baculoviruses are able to transduce brain cells efficiently in vivo and possess a very specific cell tropism in rat brain. The choroid plexus epithelial cells were transduced with high efficiency (Figure 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Baculoviruses have been shown to transduce mammalian cells in vivo, eg in carotid artery, liver, skeletal muscle and murine brain. [1][2][3][4] However, the tropism of baculoviruses in brain has remained unclear. Knowledge about the cell-type-dependent susceptibility for transduction can be utilized for targeting of transgene into certain cell types.…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to transduce various cell types in vitro and in vivo with significant efficiency. [2][3][4][5] However, efficient gene delivery still remains a challenge for baculovirus as for other gene therapy vectors in many target cells. Efficient transduction would allow high transgene expression with a lower viral load.…”
Section: Introductionmentioning
confidence: 99%
“…Intramuscular injections have previously been successfully used in transduction of mouse skeletal muscle with VSV-G displaying baculovirus, 37 and in vaccination studies, 29,38 providing data that mouse muscle might be an attractive target. Yet, in the present study, rat muscle did not result in detectable transduction, as opposed to rabbit muscle, which was transduced with VSV-GED displaying baculovirus.…”
Section: Avidin-displaying Virusmentioning
confidence: 99%